On the properties of the interstellar medium in extremely metal-poor blue compact dwarf galaxies : GMOS-IFU spectroscopy and SDSS photometry of the double-knot galaxy HS 2236+1344 - Lagos, P. (2014)
Aims. The main goal of this study is to carry out a spatially resolved investigation of the warm interstellar medium (ISM) in the extremely metal-poor blue compact dwarf (BCD) galaxy HS 2236+1344. Special emphasis is laid on analysis of the spatial distribution of chemical abundances, emission-line ratios, and the kinematics of the ISM, and to the recent star-forming (SF) activity in this galaxy. Methods. This study is based on optical integral field unit spectroscopy data from Gemini Multi-Object Spectrograph (GMOS) at the Gemini North telescope and archival Sloan Digital Sky Survey (SDSS) images. The galaxy was observed at medium spectral resolution over the spectral range from ∼4300 Å to 7300 Å. The data were obtained in two different positions across the galaxy, obtaining a total 4″ × 8″ field that encompasses most of its ISM. Results. Emission-line maps and broad-band images obtained in this study indicate that HS 2236+1344 hosts three giant H'ii regions (GH'iiRs). Our data also reveal some faint curved features in the BCD periphery that might be due to tidal perturbations or expanding ionized-gas shells. The ISM velocity field shows systematic gradients along the major axis of the BCD, with its southeastern and northwestern half differing by ∼80 km's-1in their recessional velocity over the field of view. The Hα and Hβ equivalent-width distribution in the central part of HS 2236+1344 is consistent with a very young (∼3 Myr) burst. Our surface photometry analysis reveals an underlying low surface brightness component with moderately red colors, which suggest that the galaxy has undergone previous star formation. We derive an integrated oxygen abundance of 12 + log'(O / H) = 7.53 ± 0.06 and a nitrogen-to-oxygen ratio of log'(N / O) = -1.57 ± 0.19. Our results are consistent, within the uncertainties, with a homogeneous distribution of oxygen and nitrogen within the ISM of the galaxy. The high-ionization He'ii λ4686 emission line is detected only in the central part of HS 2236+1344. Similar to many BCDs with He'ii λ4686 emission, HS 2236+1344 shows no Wolf-Rayet (WR) bump.